Research progress in traditional Chinese medicine for lymphoma: multi-pathway and multi-drug combination approaches - Yanfang Wu; Lei Zhong; Qiaoliang Wu; Liying Han; Dafei Fang (Journal of Pharmacy and Pharmacology, 2026)
Abstract Objectives Lymphoma is a prevalent hematologic malignancy with complex pathogenesis involving dysregulated signaling pathways and high treatment resistance. Traditional Chinese medicine (TCM), with its multi-component and multi-target characteristics, has shown unique value in lymphoma treatment. This review systematically summarizes the latest progress in TCM-based lymphoma therapy, focusing on its anti-cancer mechanisms and clinical application prospects. Methods A comprehensive literature search was conducted to identify peer-reviewed studies on TCM interventions for lymphoma. Key findings were synthesized regarding the multi-target mechanisms of TCM active components, synergistic effects with conventional anti-cancer therapies, and modulation of the tumour microenvironment. Challenges in the clinical translation of TCM were also analysed. Key findings TCM active components (e.g. ginsenoside Rg3, triptolide, baicalin) exert multi-target effects by regulating oncogenic pathways (NF-κB, PI3K/Akt) and inducing apoptosis, autophagy, and ferroptosis. TCM formulations demonstrate synergistic effects when combined with chemotherapy and radiotherapy, while also modulating the tumour microenvironment. Major challenges include low bioavailability, insufficient targeting, and lack of standardization for compound formulations. Conclusion TCM provides promising multi-target strategies for lymphoma, particularly when combined with conventional therapies. Future optimization should focus on novel drug delivery systems, multi-centre clinical trials, and integration of multi-omics and artificial intelligence technologies to standardize TCM-based protocols.